Exploring the Link between Neuroticism and Work–Life Balance in High-Pressure Banking Jobs - Maszura, Leni; Pratama, M. Fikri Jaka; Safitri, Yulia Nanda (Nusantara Journal of Behavioral and Social Science, 2025)
The banking sector is characterized by high work pressure, long working hours, and demanding performance targets, making it one of the most vulnerable industries to occupational stress and work–life imbalance. While organizational factors such as workload, supervisor support, and company policies are recognized as critical determinants of work–life balance (WLB), studies focusing on dispositional factors, particularly personality traits, remain limited. Neuroticism, as one of the Big Five personality dimensions, is strongly associated with emotional instability, anxiety, and rumination, which may hinder employees’ ability to manage competing role demands effectively. This study aims to examine the relationship between neuroticism and WLB among banking employees in Indonesia, where cultural values and organizational contexts may shape employees’ experiences differently than in Western settings. Using a quantitative correlational design, data were collected from 234 banking employees through purposive sampling. Neuroticism was measured using the Big Five Inventory, while WLB was assessed with the Work–Life Balance Scale. Pearson’s correlation analysis revealed a significant negative relationship between neuroticism and WLB (r = –.210, p < .001, 95% CI [–.320, –.090]), with a small-to-moderate effect size. These findings are consistent with global literature linking neuroticism to poor work–family outcomes, while also highlighting contextual factors that may buffer or intensify this relationship. Theoretically, this study contributes by extending the scope of WLB research to include personality-based determinants in a Southeast Asian context. Practically, the results suggest that banking organizations should design interventions such as stress management training, resilience-building programs, and flexible work arrangements to support employees with high neuroticism profiles.   Abstrak: Sektor perbankan dikenal memiliki karakteristik pekerjaan dengan tekanan tinggi, jam kerja yang panjang, serta tuntutan target yang ketat. Kondisi tersebut seringkali menimbulkan risiko stres kerja dan mengurangi kesempatan karyawan untuk menyeimbangkan peran antara pekerjaan dan kehidupan pribadi. Work-life balance tercapai ketika seseorang mampu memenuhi tuntutan dari kedua ranah tersebut secara proporsional. Penelitian ini bertujuan untuk mengetahui hubungan neuroticism dengan work-life balance pada karyawan perbankan. Subjek dalam penelitian ini adalah pekerja di sektor perbankan yang berjumlah 234 orang. Penelitian ini menggunakan desain penelitian kuantitatif dengan pendekatan korelasional, pengukuran variabel dilakukan menggunakan skala big-five personality dan skala-work life balance dengan format likert. Data yang diperoleh kemudian dianalisis menggunakan pearson product moment correlation. Hasil penelitian menunjukkan bahwa neuroticism berhubungan negatif secara signifikan dengan work-life balance (r = -0.210, p < .001) artinya semakin tinggi neuroticism, semakin rendah work-life balance dan sebaliknya semakin rendah neuroticism maka semakin tinggi work-life balance. Implikasi praktis dari penelitian ini adalah pentingnya organisasi perbankan menyediakan dukungan kerja yang memadai serta mengembangkan kebijakan work–life balance terutama bagi karyawan dengan profil neuroticism lebih tinggi.